2005
DOI: 10.1007/s00268-004-7822-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Delivery of Liposome‐mediated Nonviral DNA Is Less Toxic than Intraperitoneal Delivery in Mice

Abstract: Suicide gene therapy has been shown to be an effective means of destroying pancreatic cancer cells. Liposomes have been described as having better efficacy in gene delivery, and an advantage of using liposomes as gene carriers is that they can be used repeatedly in vivo. The objective of this study is to compare the effect of gene delivery routes and to determine whether systemic delivery of the rat insulin promoter (RIP)-directed suicide gene construct would permit cell-specific gene delivery in vivo. Severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Our previous studies have also demonstrated that rat insulin promoter (RIP) directed lacZ-reporter gene was express in PDX-1 producing cells such as PANC-1 cell, whereas a low expression level was detected in cell lines that produce low levels of PDX-1 proteins such as MIA PaCa2 cells. A significant cytotoxic effect of RIPTK-mediated gene therapy on PDX-1-positive cells was also found in the studies from our laboratory [26,30,45]. These studies indicate that PDX-1 protein is a crucial activator for RIP-directed gene therapy [26,30,46,47].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our previous studies have also demonstrated that rat insulin promoter (RIP) directed lacZ-reporter gene was express in PDX-1 producing cells such as PANC-1 cell, whereas a low expression level was detected in cell lines that produce low levels of PDX-1 proteins such as MIA PaCa2 cells. A significant cytotoxic effect of RIPTK-mediated gene therapy on PDX-1-positive cells was also found in the studies from our laboratory [26,30,45]. These studies indicate that PDX-1 protein is a crucial activator for RIP-directed gene therapy [26,30,46,47].…”
Section: Introductionsupporting
confidence: 58%
“…Our group has been using the rat insulin promoter to treat insulinoma and human pancreatic cancer cell line [26,30,45,47]. Our results have shown that RIPTK/GCV gene therapy with liposomal delivery system is not only able to ablate insulinoma and PANC-1 cancer cells in SCID mice, but also leads to normal glycemic controls in animal models although beta cells were not affected in these studies.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…66 The low immunogenicity potential allows for repeated injections which are necessary to achieve maximum and longterm gene expression in vivo. 52 This strategy has previously been used in a clinical trial of primary and disseminated human lung cancers by multiple monthly systemic treatments of a tumor suppressor gene using the same liposome vector as used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidants stimulate the generation of Ca 2+ signals in part through the activation of calcium channels in both mammalian cells and in plants, and these signals activate a series of biological and physiological processes (Foreman et al, 2003;Wang et al, 2005). Nox-generated ROS activates Ca 2+ signaling in G. lucidum (Mu et al, 2014).…”
Section: Gpx Affects Cytosolic Ca 2+ Levels Via Rosmentioning
confidence: 99%